Molecular Phylogenetics and Population Genetics of the Dengue Vector Aedes aegypti From the Arabian Peninsula. Issue 6 (27th July 2021) - Khater, Emad I M; Baig, Farrukh; Kamal, Hany A; Powell, Jeffery R; Saleh, Amgad A
Abstract: Aedes aegypti mosquito is the principal dengue vector in the Kingdom of Saudi Arabia (KSA); however, no study has addressed its ecology and population structure yet. Therefore, we report on Ae. aegypti phylo- and population genetics using three DNA markers: COI, ND4, and rDNA-ITS2. Sampling the immature stages of Ae. aegypti revealed that water storage tanks (34.3% of habitats) were the most productive and contained 33% of immatures stages. Other important habitats included containers for wastewater drainage (including air-conditioning and water cooler trays) and containers associated with ornamentation. Shallow water leakage spots (2.7% of habitats, 8% of immatures) can be considered rare-but-epidemiologically-important containers. Neighbor-joining (NJ) phylogenetic analysis of Ae. aegypti identified 8, 14, and 9 haplotypes of COI, ND4, and ITS2, respectively, and revealed high levels of genetic variation in Ae. aegypti populations of KSA. Global distribution of haplotypes also indicated multiple gene introductions into these populations, with high levels of intra-population genetic variation and continuous gene exchange. The neutrality values indicated a deficiency of alleles and suggested that the KSA Ae. aegypti loci tested did not follow a neutral model of molecular evolution. Fst values and AMOVA indicated that most of the genetic variation in the KSA Ae. aegypti populations is due to intra- rather than inter-population differences. This is the first comprehensive report on the phylo- and population genetics of Ae. aegypti from the Arabian Peninsula. This information expands our understanding of the ecology and population dynamics of this important arboviral vector for informed control efforts.